Diabetes and Chronic Heart Failure: From Diabetic Cardiomyopathy to Therapeutic Approach - Cas, A. D.; Spigoni, V.; Ridolfi, V.; Metra, M. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2013)
Diabetes and chronic heart failure are interrelated conditions with major medical and economic impact that have to be treated as a distinct entity. Several pathological mechanisms have been investigated and proposed to explain the structural and functional changes associated with diabetic cardiomyopathy. These mechanisms are likely to act synergically and may potentiate one the other. This review outlines recent advances in the pathophysiological mechanisms implicated in the development and progression of diabetic cardiomyopathy and in current therapeutic strategies.
Keywords: Chronic heart failure